Integrated nutrient management for maize-soybean cropping system - Gezahegn, Almaz Meseret (2016)
Low soil fertility due to monocropping, inadequate fertilizer application, and biomass removal are recognized as the major causes for declining maize and soybean yield. In this regard, two field experiments, one laboratory experiment and economic study of the alternative treatments were conducted at Universiti Putra Malaysia. The first experiment was carried out to evaluate the effect of combined application of poultry manure and inorganic fertilizer on yield, nutrient uptake and quality of maize and soybean intercrops and fertility status of soil. Treatments comprised of combinations of three cropping systems (sole maize, sole soybean, and maize + soybean) and four nutrient management (control, 100% NPK, 100% poultry manure (PM) and 50% NPK + 50% PM). The experiment was laid out in a randomized complete block design (RCBD) with three replications. The number of plants per plot in sole maize, sole soybean and maize + soybean intercropping treatments were 144, 240 and 192, respectively. Results showed that maize + soybean intercropping had greater yield and monetary return than monocropping based on land equivalent ratio (LER) and monetary advantage index (MAI). The combination of 50% NPK+50% PM fertilizer increased maize (28,264 kg/ha) and soybean (3,637 kg/ha) yield to the same level as 100% NPK (28,340 kg/ha and 3,475 kg/ha, respectively) but using 100% PM alone cannot increase the yield to the same level as 100% NPK. Combined application of 50% NPK + 50% PM increased nutritive quality over sole application of either fertilizer. Soil fertility was improved in sole soybean and intercropping of maize with soybean with application of PM alone or combined with NPK fertilizer. The second experiment was conducted by using the plots of the first experiment for each treatment to determine the residual effect of organic manures with supplemental inorganic fertilizers on the performance of the succeeding maize crop and on fertility status of soil. The experiment comprised of 14 treatments, 12 based on the first experiment and two additional treatments for comparison (control and 100% NPK). The treatment was laid out in RCBD with three replications. Results revealed that incorporation of soybean residue + 100% PK (36,500 kg/ha) and soybean residue + 50% residual PM + 50% PK (37,010 kg/ha) can increase maize yield to the same level as 100% NPK (37,290 kg/ha) without addition of N fertilizer. Combined application of crop residue with a residual PM and PK fertilizer increased nutritive quality over sole application of either fertilizer. The combination of crop residue with residual PM enhanced soil pH, organic matter and nutrient availability in the soil. The third experiment was carried out to determine C and N mineralization patterns during decomposition of individual and mixed maize and soybean residue under laboratory conditions. The experiment was carried out in randomized complete design (CBD) with three replications. The treatments consisted of maize, soybean and maize + soybean residue and control (without residue). The mixture of soil and crop residue was incubated aerobically in the dark at 25oC for 90 days. The result showed the rate of decomposition of crop residue was highly influenced by the C:N ratio and the composition of the cell wall particularly the lignin content. Hence, residues containing soybean had a faster rate of decomposition and released a high amount of N (98.4 mg/kg soil and 67.9 mg/kg soil from soybean and maize + soybean residue, respectively) compared to maize residues (15.05 mg/kg soil). An economic analysis, such as partial budget, dominance, marginal and sensitivity analysis were done for different treatments. According to the economic analysis maize + soybean intercropping with the application of 50% NPK + 50% PM gave the highest net benefit (RM 68,897 ha-1) and rate of return (2169). Incorporation of soybean residue with a residual of 50% PM + 50% PK treatment also gave the highest net benefit (RM 62,507 ha-1) for maize production. Therefore, 50% substitution of inorganic fertilizer with PM for maize and soybean intercrops and substitution of N fertilizer with soybean residue and use of residual PM for the subsequent maize crop is recommended to produce economic and high-quality crop without deteriorating soil fertility.